2005
DOI: 10.1258/095646205774988118
|View full text |Cite
|
Sign up to set email alerts
|

Is triage an appropriate way of dealing with walk-in patients attending genitourinary medicine clinics?

Abstract: Genitourinary medicine services have come under severe workload pressure to deal with unprecedented demand over the past five years. Waiting times for patients wishing to access the service have increased significantly. In order to maintain open access for those who require acute attention, many services have introduced triage systems for patients who attend without appointments (walk-ins). We have evaluated a policy of triage for such patients, and the incidence of sentinel sexually transmitted infections (ST… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 7 publications
0
10
1
Order By: Relevance
“…[6][7][8] Some publications have reported on the fast track triage of asymptomatic patients, but did not examine the incidence of GU conditions. 3,5 The current study provides an insight into the general incidence of identified conditions in either groups of patients, who were asymptomatic or symptomatic of genital discharge. The rarity of publications in this field is a reflection of lack of research, and should relate to local demography.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[6][7][8] Some publications have reported on the fast track triage of asymptomatic patients, but did not examine the incidence of GU conditions. 3,5 The current study provides an insight into the general incidence of identified conditions in either groups of patients, who were asymptomatic or symptomatic of genital discharge. The rarity of publications in this field is a reflection of lack of research, and should relate to local demography.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual health and genitourinary (GU) medicine clinics are experiencing high workload, coupled with increase in trends in the diagnoses of sexually transmitted infections (STIs). Public awareness and anxiety regarding STIs, new microbiological and investigative technology have all given grounds for revisiting methods of triage, [1][2][3] some of which rely on the lack of symptoms of discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 They triaged patients according to age, symptoms and history of exposure to STIs. They found that the incidence of sentinel STIs (chlamydia and gonorrhoea) was significantly higher in those individuals who satisfied the triage criteria than in those who did not (15.8% vs 1.7%).…”
Section: Introductionmentioning
confidence: 99%
“…This system allows patients to arrive at a facility without an appointment. While walk-ins are usually only permitted in emergency situations 247 , what we are concerned with here are walk-in services motivated by patient centeredness. Little is known about the success of these walk-in facilities 248 .…”
Section: Appointment Systemmentioning
confidence: 99%